Airway ultrasound: Point of care in children—The time is now. Issue 3 (20th January 2020) - Daniel, Sam J.; Bertolizio, Gianluca; McHugh, Tobial
Abstract: Background: Point‐of‐care ultrasonography of the airway is becoming a first‐line noninvasive adjunct assessment tool of the pediatric airway. It is defined as a focused and goal‐directed portable ultrasonography brought to the patient and performed and interpreted on the spot by the provider. Successful use requires a thorough understanding of airway anatomy and ultrasound experience. Aims: To outline the many benefits, and some limitations, of airway ultrasonography in the clinical and perioperative setting. Materials and Methods: Expert review of the recent literature. Results: Ultrasound assessment of the airway may provide the clinician with valuable information that is specific to the individual airway static and dynamic anatomy of the patient. Ultrasound can help identify vocal cord dysfunction and pathology, assess airway size, predict the appropriate diameter of endotracheal and tracheostomy tubes, differentiate tracheal from esophageal intubation, localize the cricothyroid membrane for emergency airway access and identify tracheal rings for US‐guided tracheostomy. Ultrasonography is also a great tool for the intraoperative diagnosis of a pneumothorax, the visualization of the movement of the diaphragms, and quantifying the amount of gastric content. Ultrasonography signs, tips, and pearls that allow these diagnoses are highlighted. The major disadvantage of ultrasonography remains interobserver variability, and operator dependence, as it requires specific training and experience. Conclusion: Although it is not standard of care yet, there is significant potential for the integration of ultrasound technology into the routine care of the airway.